“COMPLIANCE AND CONSUMER EXPECTATIONS” (International Journal of Food and Nutritional Sciences, 2021)
Consumer rights and product safety are crucial elements in ensuring that markets function equitably and efficiently. This paper explores the intricate relationship between regulatory compliance and consumer expectations regarding product safety. It examines how regulatory frameworks have evolved to protect consumers, the gaps in these systems, and the disconnects between what consumers expect and what is delivered. This research delves into global standards, the role of regulatory bodies, and consumer perceptions, ultimately proposing a model for improved synergy between regulations and consumer trust.